Vigilantes da memória: programa intergeracional multidisciplinar de estimulação cognitiva - Gil, Gislaine (2014)
In the current demographic context, aging and neurodegenerative diseases are topics discussed in the media as important to society affairs. Aging is usually related to functional changes, but adults and seniors wishing to remain cognitively healthy, looking in preventing the most promising way to achieve the goal. This study analyzed the effect of a multidisciplinary intergenerational program of cognitive stimulation on performance in attention, memory, mood and metamemory people over thirty years, with high school, a hospital tall in the city of São Paulo. Through documentary analysis / retrospective of people who spontaneously sought the stimulation program, due to subjective memory complaints assessed before and after five months (ninety minutes of stimulation per week) with the completion of the program of tests: attention, memory, ecological scales of anxiety, mood and intensity of subjective memory complaint. The results show an improvement in the performance of psychometric tests that suggested improvement in the functioning of attention and memory, beyond the reduction of depressive and anxiety symptoms. There was no statistically significant change in this study on metamemory